The Role of Consumer Emotional Value, and Service Innovation on Consumer Purchase Decisions: TAM Theory Approach - Dedi Juniansyah; Sabri Hasan; Aditya Halim Perdana Kusuma Putra (Golden Ratio of Marketing and Applied Psychology of Business, 2023)
This study aims to analyze the influence of customer emotional value and service innovation variables on consumer purchase decisions using the Technology Acceptance Model (TAM) theory approach. This study uses a quantitative approach and uses primary data from questionnaires and secondary data. The sample in this study were 231 people spread across various provinces in Indonesia using an unlimited population. Data analysis was performed using validity test, reliability test, R-squared test, F-squared test, direct effect test, and Partial Least Square (PLS) hypothesis submission. The results show that the Technology Acceptance Model (TAM) has a positive and significant effect on Emotional Value and Service Innovation, as well as on Consumer Purchase Decisions through the mediation of Emotional Value and Service Innovation. However, the Technology Acceptance Model (TAM) does not have a positive and significant effect on Consumer Purchase Decisions directly.